2007
DOI: 10.4103/0019-5545.37668
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine: Current perspective

Abstract: The author conducted a review of studies that compared the efficacy, tolerability and indication for the use of clozapine in current perspectives for the treatment of resistant schizophrenia/ partial responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 78 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…This side effect is not considered to be dose dependent, but it may be the result of an idiosyncratic drug reaction. 7 , 8 There are case reports in the literature of patients that developed agranulocytosis due to several other antipsychotic medications. 5 , 6 Clinical trials and case reports have demonstrated that G-CSF is useful in treating clozapine-induced granulocytopenia by stopping agranulocytosis and increasing the number of granulocytes and macrophage precursors in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…This side effect is not considered to be dose dependent, but it may be the result of an idiosyncratic drug reaction. 7 , 8 There are case reports in the literature of patients that developed agranulocytosis due to several other antipsychotic medications. 5 , 6 Clinical trials and case reports have demonstrated that G-CSF is useful in treating clozapine-induced granulocytopenia by stopping agranulocytosis and increasing the number of granulocytes and macrophage precursors in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, use of fluoroquinolones leads to the risks of adverse effects of interactions with psychotropic drugs (Fish, 2001). Ciprofloxacin apparently does not alter the elimination of some tranquilizers drugs like diazepam (Wijnands et al, 1990) however, causes clinically interaction with clozapine (Markowitz et al, 1997) , an anti-psychotropic drug usually prescribed for treatment of schizophrenia, bipolar disorder, psychotic refractory depression and Parkinson´s disease in psychotic patients (Solanki et al, 2007). As reported in a randomized double blind cross over study in schizophrenic inpatients, ciprofloxacin strongly inhibited clozapine metabolism associated to the increase in serum levels of clozapine and a metabolic derivative, Ndesmethylclozapine, (Raaska et al, 2000).…”
Section: Interaction Of Antibiotics With Drugs Used For Psychiatric Tmentioning
confidence: 99%
“…Efficacy data for other SGA's in the treatment of refractory schizophrenics were inconclusive. [ 28 ]…”
Section: Treatment Of Resistant Schizophrenia With Atypical Antipsychmentioning
confidence: 99%